KELAYAKAN MEDIA PEMBELAJARAN E-MODUL AKSESORI DARI SAMPAH ANORGANIK - Alfiani, Nadia; Listiani, Sri; Prabawati, Melly (Practice of Fashion and Textile Education Journal, 2023)
This study aims was to make learning media e-module accessories from inorganic waste and to assess learning media e-module accessories from inorganic waste. The method used in this research is the Pre-Experimental method with the form of One Shot Case Study design. The data analysis technique used is descriptive quantitative. Used a single variable the assessment of learning media e-module accessories from inorganic waste. This research was rated by material experts and media experts with the indicators was used 5 characteristic of module, namely self instruction, self contained, stand alone, adaptive, user friendly and used aspect of learning media, namely aspects of media display, aspects of media integration with material, and aspects of operational or media interactivity. The result stated that in material assesment gets percentage of 89,25% and in media assessment gets percentage of 86,5%. The avearge percentage in material assesment and media assessment gets 88% with the higest aspect is adaptive and user friendly.